2015
DOI: 10.1002/wnan.1338
|View full text |Cite
|
Sign up to set email alerts
|

Product quality for nanomaterials: current U.S. experience and perspective

Abstract: In recent years, there has been an increased focus on developing novel drug delivery systems and targeted therapies through the use of nanotechnology and nanomaterials. Such focus is translating to an increasing number of investigational new drug (IND) applications, new drug applications (NDAs), and abbreviated new drug applications (ANDAs) for drug products containing nanomaterials to the United States Food and Drug Administration (FDA). Although subject to the same rigorous regulatory standards and regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 56 publications
0
37
0
1
Order By: Relevance
“…Particle size is a frequently requested characteristic when discussing nanomaterials 9 . It has been repeatedly demonstrated that the size of nanomaterials can impact absorption, biodistribution and excretion [38][39][40] .…”
Section: Particle Size Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particle size is a frequently requested characteristic when discussing nanomaterials 9 . It has been repeatedly demonstrated that the size of nanomaterials can impact absorption, biodistribution and excretion [38][39][40] .…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Such diversity is a result of both the evolving nature of the field as well as the method used to obtain the data. For example, a D50 value could be supplied for data arising from laser diffraction, whereas a Z ave value would be supplied for data arising from DLS, or a mean for the apparent diameter for electron microscopy data 9 .…”
Section: Particle Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying this or a similar approach in preclinical studies helps to obtain reproducible drug batches [18][19][20]. …”
Section: Chemical Chemical and Microbiological Aspects Such As Macmentioning
confidence: 99%
“…Studies at this stage may be the first tests of a drug product's translational potential and will provide a foundation for further preclinical development, to eventually include tests geared at meeting regulatory requirements for an Investigational New Drug (IND) application (4).…”
Section: Introductionmentioning
confidence: 99%